The boatowner's guide to GMDSS and marine radio : (International Marine/McGraw-Hill, 2006)
The new digital Global Maritime Distress and Safety System (GMDSS) is revolutionizing emergency communications and international search-and-rescue at sea. Clearly and concisely, this one-of-a-kind guide presents what you should know about using digital marine radios for emergency assistance and enhanced safety.